Pengaruh Digital Marketing dan Brand Awareness terhadap Keputusan Pembelian pada Produk Kofieboy - Dwiputri, Rika; Isyanti, Puji; Sumarni, Neni (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The development of the coffee shop business in Indonesia shows quite rapid development, one of which is in Karawang City. The phenomenon experienced by the Kofieboy shop is the rise and fall of income and competition over the last few years. After the pandemic, Kofieboy is trying to increase his income to return to normal times by using digital marketing which utilizes social media such as Instagram, YouTube, Facebook and TikTok. Apart from that, Kofieboy also sells through e-commerce such as Grabfood, Gofood and Shopeefood. This research aims to determine the partial or simultaneous influence of digital marketing and brand awareness on purchasing decisions for Kofieboy products. The method used in this research is a quantitative method. This research was conducted on kofieboy Karawang. The sample for this research was 100. The sampling technique in this research used the saturated sampling method. The analysis model used in this research is a multiple linear regression analysis model using the f test and t test with a significance level of 5%. The research results show that there is a partial influence between digital marketing on increasing purchases with the t table value (5.348 > 1.661 or tcount > ttable). Meanwhile, there is a partial influence of work discipline on employee performance with t table (2.507 > 1.661).